Immobilized Subpopulations of Leaf Epidermal Mitochondria Mediate PENETRATION2-Dependent Pathogen Entry Control in Arabidopsis. Issue 1 (31st December 2015) - Fuchs, Rene; Kopischke, Michaela; Klapprodt, Christine; Hause, Gerd; Meyer, Andreas J.; Schwarzländer, Markus; Fricker, Mark D.; Lipka, Volker
Abstract : Powdery mildew attack induces arrest of mitochondria at sites of attempted invasion, peripheral accumulation of the myrosinase PEN2, and redox imbalances in the matrix of the immobilized mitochondria. Abstract: The atypical myrosinase PENETRATION2 (PEN2) is required for broad-spectrum invasion resistance to filamentous plant pathogens. Previous localization studies suggested PEN2-GFP association with peroxisomes. Here, we show that PEN2 is a tail-anchored protein with dual-membrane targeting to peroxisomes and mitochondria and that PEN2 has the capacity to form homo-oligomer complexes. We demonstrate pathogen-induced recruitment and immobilization of mitochondrial subpopulations at sites of attempted fungal invasion and show that mitochondrial arrest is accompanied by peripheral accumulation of GFP-tagged PEN2. PEN2 substrate production by the cytochrome P450 monooxygenase CYP81F2 is localized to the surface of the endoplasmic reticulum, which focally reorganizes close to the immobilized mitochondria. Exclusive targeting of PEN2 to the outer membrane of mitochondria complements the pen2 mutant phenotype, corroborating the functional importance of the mitochondrial PEN2 protein subpool for controlled local production of PEN2 hydrolysis products at subcellular plant-microbe interaction domains. Moreover, live-cell imaging shows that mitochondria arrested at these domains exhibit a pathogen-induced redox imbalance, which may lead to the production of intracellular signals.